Diskriminasi Petugas Kesehatan terhadap Orang Dengan HIV-AIDS di Provinsi Kepulauan Bangka Belitung - Darmoris, Darmoris; Shaluhiyah, Zahroh; Mustofa, Syamsulhuda Budi (Jurnal Promosi Kesehatan Indonesia, 2011)
Based on reports of Bangka Belitung Provincial Health Office in 2008 that there is still discrimination against PLHA. The aim of this study was to analyze and identify the factors influencing the existence of discrimination by health workers to PLHA at the Provincial Hospital of Bangka Belitung Islands. This study was an explanatory research using cross sectional approach with qualitative and quantitative combination. The results showed 42.4% of responder are still discriminating against PLHA. quantitative sampel 250 participants, qualitative 2 participants. Form of discrimination is the use of personal protective equipment only when dealing with HIV (59.2%), sterilization of equipment used in addition to Persons With HIV-AIDS (57.2%), giving a specific code (55.6%), separated equipment (50%), and placing PLHA in its place, talk about their HIV status to others (15.6%), 6% of responder refused to serve PLHA. Variable that most affected: hospital policies in the care of Persons With HIV-AIDS.